Palliative Caregivers' Spirituality, Views About Spiritual Care, and Associations With Spiritual Well-Being: A Mixed Methods Study. (April 2020) - O'Callaghan, Clare; Seah, Davinia; Clayton, Josephine M.; Welz, Martina; Kissane, David; Georgousopoulou, Ekavi N.; Michael, Natasha
Background: Spiritual care is integral to palliative care. It engenders a sense of purpose, meaning, and connectedness to the sacred or important and may support caregiver well-being. Aim: To examine caregivers' spirituality, religiosity, spiritual well-being, and views on spiritual/religious support. Design: A mixed-methods study across 4 Australian sites, recruiting caregivers of patients with a life expectancy of under 12 months. The anonymous semistructured questionnaire used included research team developed and adapted questions examining religion/spirituality's role and support and views on hospitals supporting spiritual/religious requirements. It additionally included the Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being Scale (FACIT-Sp-12). Results: One hundred nine caregivers participated (47.4% responded). Median spiritual well-being was 30.5 on FACIT-Sp-12. Religious affiliation was associated with higher Faith subscores ( P < .001). Spirituality was very important to 24.5%, religiosity to 28.2%, and unimportant to 31.4% and 35.9%, respectively. Caregivers prayed ( P = .005) and meditated ( P = .006) more following patients' diagnoses, gaining comfort, guidance, and strength. Caregivers whose spiritual/religious needs were met to moderate/full extent by external religious/faith communities (23.8%) reported greater spiritual well-being ( P < .001). Hospitals supported moderate/full caregiver spiritual needs in 19.3%. Pastoral care visits comforted 84.4% of those who received them (n = 32) but elicited discomfort in 15.6%. Caregivers also emphasized the importance of humane staff and organizational tone in supporting spiritual care. Conclusions: Hospital-based spiritual care providers should seek to identify those who seek pastoral or religiously orientated care. Genuine hospitality of showing concern for the other ensures the varied yet inevitably humanist requirements of the caregiver community are met.